92.9k views
4 votes
5x + 7y = -29 y = x + 1

User DumbPy
by
6.2k points

1 Answer

4 votes

Answer:

(x, y) = (-3, -2)

Explanation:

Perhaps this is a system of equations you want the solution for.

Since you have an expression for y, substitution is a viable approach.

5x +7(x+1) = -29 . . . . . . substitute for y

12x = -36 . . . . . . subtract 7 and simplify

x = -3 . . . . . . . . . divide by 12

y = (-3) +1 = -2 . . . use the expression for y

The solution is (x, y) = (-3, -2).

5x + 7y = -29 y = x + 1-example-1
User Daniel Shapero
by
5.6k points